WATER AND MOISTURE RELATED PROPERTIES OF BEECH (Fagus sylvatica L.) VENEER TREATED WITH SILICONE COMPOUNDS - Hien Mai, Trinh (Journal of Forestry Science and Technology, 2018)
Beech (Fagus sylvatica L.) veneers were impregnated with 10% solid content of silicone compounds (amino and epoxy functional polysiloxane) from textile industry. The impregnation process included two steps: vacuum of 60 mbar for 30 min and followed by 2h veneer storing in the solutions at atmospheric pressure. Then, the veneers were pre-dried at 40°C for 24h and cured at 140°C for 2h in a drying-oven before testing water and moisture absorption. The results showed that water repellence effectiveness (WRE) of the treated veneers within each submersion were quite high (up to 70%) in the initial submersion phases of 1 min, 10 min, 1h, 2h, 4h and then lessened gradually in the submersion phases of 24h. After vacuum support and soaking in water overnight (24h), WREs (at water saturation) got the lowest values ranging from micro amino silicone ASE 8130 (3%) to macro amino silicone ASE 8730 (10%). The wetting-drying cycles after each submersion did not result in significant change of WREs in the second, third and fourth submersion although weight loss of each treatment increased from the first cycle to the fourth submersion. After the fourth submersion, silicone SIN treated veneers got the highest weight losses (4%) whereas two silicones ESE 6960 and ASE 8730 revealed the lowest weight loss (1.4 and 1.6%, respectively). When stored in an environment of 30, 65, 90% relative humidity and 20oC, all of the silicone treated veneers get minor lower equilibrium moisture content EMCR (0 - 1.7%) and radial swelling RS (0 - 0.7%) than the control veneers at different levels.